An In-Depth Analysis of Peritoneal Dialysate Effluent Composition with a Deep-UV-LED-Based Affordable Optical Chromatographic Sensor - Nikolay Ovsyannikov; Georgii Konoplev; Artur Kuznetsov; Alar Sünter; Vadim Korsakov; Oksana Stepanova; Milana Mikhailis; Roman Gerasimchuk; Alina Isachkina; Zarina Rustamova; Aleksandr Frorip (Engineering Proceedings)
It was shown earlier that the use of fast protein and metabolites liquid chromatography (FPMLC) and low-cost deep UV–LED-based optical chromatographic sensors with PD-10 desalting columns as a separation element can facilitate the monitoring of patients on chronic peritoneal dialysis (PD). Previously, we established that the first peak in the FPMLC chromatograms of effluent dialysate is mainly responsible for proteins and could be used for the assessment of peritoneal protein loss in patients on PD, while the origin and clinical significance of the other two peaks still remain unclear. Optical absorption and fluorescence spectroscopy in the UV and visible regions of 240…720 nm were used for the analysis of PD effluent chromatographic fractions collected from a drainpipe of the sensor with photometric detection at 280 nm; chromatograms of twenty dialysate samples were processed. The absorption and fluorescence spectra of the first fraction demonstrated peaks at 270 nm and 330 nm, respectively, which is typical for proteins. The absorption spectra of the third fraction revealed the characteristic maxima of creatinine and uric acid, while the fluorescence spectra showed the characteristic peak of indoxyl sulfate 375 nm at 270 nm excitation. The second fraction had a single, extremely wide absorption band, strong fluorescence was observed at 440–450 nm while excited at 370 nm. Such spectral characteristics are typical for advanced glycation end products (AGE). Thus, it was demonstrated that deep UV–LED-based affordable chromatographic sensors could provide significantly more information about the composition of PD effluent dialysate than just the total protein concentration, including the contents of clinically significant metabolites, e.g., indoxyl sulfate and AGE. Moreover, the introduction of optical fluorescence detection could significantly improve the capabilities of such devices.